New Insights From Recent Studies in Historical Astronomy: Following in the Footsteps of F. Richard Stephenson A Meeting to Honor F. Richard Stephenson on His 70th Birthday - Orchiston, Wayne; Green, David A.; Strom, Richard (Astrophysics and Space Science Proceedings, 2015)
This book contains papers from a conference held to celebrate the 70th birthday of one of the world's foremost astronomical historians, Professor F. Richard Stephenson, the latest recipient of the American Astronomical Society's highest award for research in astronomical history, the LeRoy Doggett Prize. Reflecting Professor Stephenson's extensive research portfolio, this book brings together under one cover papers on four different areas of scholarship: applied historical astronomy (which Stephenson founded); Islamic astronomy; Oriental astronomy; and amateur astronomy.  These papers are penned by astronomers from Canada, China, England, France, Georgia, Iran, Japan, Lebanon, the Netherlands, Portugal, Thailand and the USA. Its diverse coverage represents a wide cross-section of the history of astronomy community.  Under discussion are ways in which recent research using historical data has provided new insights into auroral and solar activity, supernovae and changes in the rotation rate of the Earth. It also presents readers with results of recent research on leading historical figures in Islamic and Oriental astronomy, and aspects of eighteenth and nineteenth century Australian, British, German and Portuguese amateur astronomy, including the fascinating 'amateur-turned-professional syndrome'.